2013
DOI: 10.1055/s-0033-1344794
|View full text |Cite
|
Sign up to set email alerts
|

Updating the management of patients with rectal neuroendocrine tumors

Abstract: Rectal neuroendocrine tumors (NETs) account for approximately one-third of all digestive NETs, with an increasing incidence and good overall prognosis. Although recent guidelines have been published, endoscopic techniques have expanded substantially and the most recent reports should be taken into account for clinical practice. The objectives of this report were to review the latest advances on prognosis, pre-interventional explorations, treatment-with particular focus on endoscopy-and surveillance of well-dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 36 publications
(96 reference statements)
2
93
0
12
Order By: Relevance
“…Currently, several different techniques are available for ER of rectal NETs [23][24][25][26][27][28][38][39][40][41]. We have reported an excellent R0 resection rate of ESMR-L as compared with the rate obtained with polypectomy and conventional EMR [39,40].…”
Section: Discussionmentioning
confidence: 84%
“…Currently, several different techniques are available for ER of rectal NETs [23][24][25][26][27][28][38][39][40][41]. We have reported an excellent R0 resection rate of ESMR-L as compared with the rate obtained with polypectomy and conventional EMR [39,40].…”
Section: Discussionmentioning
confidence: 84%
“…Risk factors for metastasis include tumor size, muscularis propria invasion, histologic grade (Ki-67 index and mitotic count), lymphovascular invasion, neural invasion, and atypical endoscopic features[10,16]. In particular, presence of a > 10-mm tumor size and lymphatic invasion strongly corresponded to LN metastasis, with the rate of LN metastasis increasing to 16% with either one of these two risk factors, and further increased to as high as 77% in patients with both risk factors[17].…”
Section: Discussionmentioning
confidence: 99%
“…The complete resection rate pooled from 14 studies has been found to be 59.1% with polypectomy or EMR for RNETs (range 17-90%) [10]. To achieve clear resection margins, more advanced techniques such as endoscopic submucosal dissection (ESD), endoscopic submucosal resection with a ligation device (ESMR-L; fig.…”
Section: Er Techniquesmentioning
confidence: 99%
“…Therefore, recent guidelines recommend additional treatment for RNETs if LVI is presented after ER [10,17]. Previous studies have shown that small RNETs have a very low incidence of LVI [18,19,20,21].…”
Section: Lymphovascular Invasion In Small Rnetsmentioning
confidence: 99%
See 1 more Smart Citation